Kant's theory of experience - Stephenson, A; Andrew Stephenson (2013)
In this thesis I present and defend an interpretation of Kant’s theory of experience as it stands from the viewpoint of his empirical realism. My central contention is that Kant’s is a conception of everyday experience, a kind of immediate phenomenological awareness as of empirical objects, and although he takes this to be representational, it cannot itself amount to empirical knowledge because it can be non-veridical, because in such experience it is possible to misrepresent the world. I outline my view in an extended introduction. In Part I I offer a novel interpretation of Kant’s doctrine of sensibility and sensation. Utilizing a data-processor schematic as an explanatory framework, I give an account of how outer sense, as a collection of sensory capacities, is causally affected by empirical objects to produce bodily state sensations that naturally encode information about those objects. This information is then processed through inner sense to present to the understanding a manifold of mental state sensations that similarly encode information. I also give accounts of how the reproductive imagination operates in hallucination to produce sensible manifolds in lieu of current causal affection, and of the restricted role that consciousness plays at this low level of cognitive function. In Part II I turn to the role of the understanding in experience. I offer a two-stage model of conceptual synthesis and explain how Kant’s theory of experience is a unique blend of conceptualist and non-conceptualist elements. I show that it explains how our experience can provide us with reasons for belief while at the same time accounting for the fact that experience is what anchors us to the world. Finally, I return to non-veridical experience. I confront recent naïve realist readings of Kant and argue that, for Kant, the possibility of non-veridicality is built into the very nature of the human mind and the way it relates to the world.